The management game of communication - Simcic Brnn, Peggy; Romenti, Stefania; Zerfass, Ansgar, 1965-; Villa, Virginia (Bingley, U.K. : Emerald, 2016)
We still see many communication graduates with little business knowledge and business graduates with little communication knowledge. This schism leads communication scholars to assume that better communication is an end in itself while management see it as a means to an end it must somehow contribute to the bottom line. How can strategic communication and public relations support corporations? What can communicators learn from management disciplines? Moreover, how should universities and business schools deal with the need to integrate research and education from different disciplines to advance the field? This book addresses these challenges and offers some answers. The contributions from primarily European countries were selected from a large number of peer-reviewed contributions for the 2015 congress of the European Public Relations Education and Research Association hosted by BI Norwegian Business School in Oslo. The chapters explore challenges of linking both fields; discuss research focusing on communication, leadership and organisational goals; and present findings from current research in corporate communication.
Business knowledge as limited success factor for communication managers: results of a survey in the German-speaking context / Holger Sievert, Lars Rademacher, Anna Weber -- Public relations: economics vs. communication science - effects of education on the practice in Austrian non-profit organisations / Astrid Spatzier -- Communication and management: an obvious relationship? the BA curricula in communication management in Flanders / Anne-Marie Cotton, Els van Betsbrugge -- Silo thinking is out, fortress invaded: running a communication program at a business school / Anne Kankaaranta, Leena Louhiala-Salminen -- Communication courses in MBA programmes: an analysis of curricula of business schools in the United States and Europe / Ralf Spiller, Stefan Weinacht, Andreas Ko<U+0308>hler -- Bulwark of the company or advocate of stakeholders? public relations strategies between influencing and consulting / Olaf Hoffjann, Philine Hachmeister -- Communicating the leadership status of organisations: a cross-national study in 10 European countries / Ansgar Zerfass, Markus Wiesenberg -- Communication professionals and organisational decision-making: a Finnish study of practitioner roles / Markus Mykka<U+0308>nen -- Putting communication and soft tools into managerial scoring scope: hurdles and opportunities for combining communication and managerial insights (KPIS) / Ton Baetens, Jan Maessen -- Creating shared value through communication: a case study analysis of Barilla / Emanuele Invernizzi, Stefania Romenti, Grazia Murtarelli -- Exploring the magic of mentoring: career planning for the public relations profession / Ralph Tench, Lucy Laville, Juliane Kiesenbauer -- Change communication: emerging perspectives for organisations and practitioners / Ivana Crestani -- Dialogue for strategic decision-making processes: an idea model / Elena Gutie<U+0301>rrez-Garci<U+0301>a, Mo<U+0301>nica Recalde -- Corporate communication in SMEs: unveiling an ignored field of practice / Ansgar Zerfass, Luisa Winkler.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Public relations; Communication studies; Business communication